Orthodontic treatment in impacted maxillary canines. A review of the literature - Aquino-Valverde, Alexandra J. (2021)
The prevalence of impacted maxillary canines is 1 to 3%, with approximately 50% of impacted canines causing root resorption of adjacent teeth. If the permanent canine has not acquired its correct position, evaluation by an orthodontist is necessary to determine the most adequate treatment. Surgery and orthodontic treatment are used for the treatment of impacted canines in the maxilla affecting permanent dentition. The selection of the most adequate treatment to achieve the correct position of the canine tooth depends on the position of the canine. This article summarizes the different techniques available and describes their advantages and cost-benefit considerations. The objective of this literature review is to describe the etiology of impacted maxillary canines and provide an update of the information on orthodontic treatments available for these patients.